2017
DOI: 10.1080/09513590.2017.1320384
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy comparison of oral rosuvastatin versus oral progesterone and bevacizumab on regression of surgically endometriotic implants in rats

Abstract: This study hypothesizes that oral rosuvastatin, oral dienogest and intraperitoneal bevacizumab might improve endometriosis in randomly selected female Wistar albino rats with surgically endometriotic implants. Thirty female Wistar albino rats with surgically endometriotic implants were randomized into three treatment groups: oral rosuvastatin (20 mg kg/day; oral rosuvastatin group 1; n = 10), oral progesterone (dienogest group 2; n = 10) and intraperitoneal bevacizumab (2.5 mg/kg of single intraperitoneal inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Furthermore, according to Ricci et al, Bevacizumab significantly inhibited cell proliferation in lesions, reduced vascular density and increased the apoptotic cell percentage (16). Also, Kebapcilar et al showed higher reduction for the glandular epithelium and uterine vessels compared to controls treated with progesterone (18). Interestingly, Bevacizumab treatment did not affect ovarian reserve assessed by follicle quantification at histochemistry of ovarian serial sections (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, according to Ricci et al, Bevacizumab significantly inhibited cell proliferation in lesions, reduced vascular density and increased the apoptotic cell percentage (16). Also, Kebapcilar et al showed higher reduction for the glandular epithelium and uterine vessels compared to controls treated with progesterone (18). Interestingly, Bevacizumab treatment did not affect ovarian reserve assessed by follicle quantification at histochemistry of ovarian serial sections (21).…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments already showed beneficial effects both in the treatment and prophylaxis of endometriosis relapse (16)(17)(18)(19)(20)(21). The effect of vascular endothelial growth factor inhibition on the volume of endometrial implants was described by all these authors.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis progression relies heavily on angiogenesis. Bevacizumab, a recombinant humanized monoclonal antibody against vascular endothelial growth factor (VEGF), resulted in larger regression of endometriotic implants than DNG when injected along with oral rosuvastatin in mice [142] . Preclinical studies have shown the effects of various tyrosine kinase inhibitors.…”
Section: Investigational Therapeutic Optionsmentioning
confidence: 99%
“…It has been found that bevacizumab suppresses endometriotic implants and prevents their progression in rat models of endometriosis without affecting the ovarian reserve, and furthermore, its efficacy is comparable to GnRH-a and higher than oral progesterone compounds. 71,93,94 Moreover, it reduces vascular density and peritoneal fluid VEGF concentration. 95 However, administration of bevacizumab carries a high risk of severe adverse effects (gastrointestinal perforation, thrombosis, severe bleeding, impaired kidney function, and wound healing), which are unlikely to be acceptable from patients with a nonmalignant disease.…”
Section: Anti-vegf Moleculesmentioning
confidence: 99%
“…Recent animal studies have also explored whether bevacizumab, a recombinant humanized anti-VEGF monoclonal antibody that is widely used in colorectal cancer, could be used against endometriosis due to its antiangiogenic features. It has been found that bevacizumab suppresses endometriotic implants and prevents their progression in rat models of endometriosis without affecting the ovarian reserve, and furthermore, its efficacy is comparable to GnRH-a and higher than oral progesterone compounds 71,93,94 . Moreover, it reduces vascular density and peritoneal fluid VEGF concentration 95 .…”
Section: Novel Antiangiogenic Agents For Management Of Women With End...mentioning
confidence: 99%